2010
DOI: 10.1001/archpediatrics.2009.284
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care of Children With Brain Tumors

Abstract: Participants: Twenty-five parents of 17 children who had died of brain tumors. Intervention: Parents participated in 3 semistructured focus group interviews. Main Outcome Measures: Themes identified through thematic analysis of interview transcripts. Results: Qualitative analysis identified 3 primary themes. (1) Parents described the dying trajectory of their child as characterized by progressive neurologic deterioration, with the loss of the ability to communicate as a turning point. Parental coping mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
141
0
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(155 citation statements)
references
References 27 publications
3
141
0
11
Order By: Relevance
“…3 Although much has been made of the high cost of dying in hospitals and nursing homes, 4 home-based dying often involves significant out-of-pocket costs in addition to difficult tasks and responsibilities for family caregivers. 5,6 Most EOL care in the home is provided by family caregivers, often with little assistance from others, including formal home care providers. 5,7,8 Regardless, a shift from hospital to home-based death and dying is occurring in Canada and elsewhere, notably Britain and the United States.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although much has been made of the high cost of dying in hospitals and nursing homes, 4 home-based dying often involves significant out-of-pocket costs in addition to difficult tasks and responsibilities for family caregivers. 5,6 Most EOL care in the home is provided by family caregivers, often with little assistance from others, including formal home care providers. 5,7,8 Regardless, a shift from hospital to home-based death and dying is occurring in Canada and elsewhere, notably Britain and the United States.…”
Section: Introductionmentioning
confidence: 99%
“…[16] For example, patients with cancer who are able to develop a sense of peace and equanimity in their cancer experience tend to have better quality of life [13,27] and better psychological health. [13,26,27,28,29] In children, spirituality has been defined as the ability to derive personal value and transcend beyond the self through relationships with others.…”
Section: Spirituality In Patients' Cancer Journeymentioning
confidence: 99%
“…[37,19] Therefore, pediatric cancer experience may create significant challenges for health care professionals and the children's parents, supporting the need for increased awareness of the distinct issues in the palliative care of children with cancer and for early anticipatory guidance provided for families. [16] Spirituality helping family cope with the pediatric cancer experience Despite increasing survivorship, childhood cancer is nonetheless still a very traumatic phenomenon. To the parents it could be like to live through and bear witness to their child actively dying.…”
Section: J Pediatr Oncol Nursmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2010 study of 25 parents whose children died from brain tumours found that parents use hope as a coping mechanism. 9 It is therefore difficult to balance hope for a cure with hope for the comfort and dignity of the child.…”
mentioning
confidence: 99%